Use of Tissue Plasminogen Activator in Catheters Used for Extracorporeal Renal Replacement Therapy. (17th January 2014) - Langston, C.; Eatroff, A.; Poeppel, K.
<x xml:space="preserve">Abstract</x> Background Intraluminal thrombosis of central venous catheters used for renal replacement therapy (RRT) decreases the ability to provide adequate treatment. Alteplase is a recombinant tissue plasminogen activator that has been used to improve the function of catheters used for RRT in humans. Objectives To retrospectively review alteplase instillation in dysfunctional catheters used for RRT in dogs and cats. Animals Seventeen dogs and 8 cats receiving RRT for kidney failure. Methods Medical records of patients in which alteplase was used for RRT catheter dysfunction from 2004 to 2012 were retrospectively reviewed to characterize reasons for use, improvement in function, increase in blood flow, and duration of improvement. Results Alteplase was instilled 43 times in 29 catheters, most commonly because of suspicion that the catheter would not provide sufficient flow on the next treatment (n = 21). The second most common reason was inability to start a dialysis treatment (n = 12). Catheter function improved after alteplase instillation in 34 of 43 treatments (79%). Median blood flow rate increased by 13% (18 mL/min) in the dialysis session after alteplase instillation. Seven of 29 catheters (24%) were treated with alteplase on >1 occasion (median time to second treatment, 8 days), and 1 catheter had to be replaced because of intractable dysfunction. Conclusions and Clinical Importance Alteplase is effective at improving function of central venous catheters used to provide RRT, but the results are short‐lived.